2021
DOI: 10.3390/vaccines10010025
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vaccine Hesitancy in Japan across Five Months during the COVID-19 Pandemic and Its Related Factors

Abstract: Although vaccination is a particularly important countermeasure against the coronavirus disease 2019 (COVID-19), vaccine hesitancy may be a barrier to an effective vaccination program. It is understood that attitude towards vaccines is not a simple binominal decision between hesitancy and acceptance, but a continuum with a wide range of related factors. It is also likely to change depending on the present situation. Therefore, this study aimed to examine changes in vaccination attitudes across a five-month per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 33 publications
4
39
1
1
Order By: Relevance
“…Our finding of low COVID-19 vaccine acceptance was inconsistent with what was reported from other university students in other countries like Saudi Arabia, [6]; Lebanon, [31]; Italy, [32]; Japan, [33]; the United Kingdome, [26]; Australia, [36] and France, [37] (90.4%, 87%, 86.1%, 85.5%, 73.5%, 60.5%, and 58.0%, respectively). Moreover, some studies were in line with our findings showed a low rate of COVID-19 vaccine acceptance like Turkey with 36.6% acceptance, [38]; Egyptian students 35%, [39]; Jordan with 34.9%, [22] and 33 % of the Iraqi university students [40].…”
Section: Factors Related To Covid-19 Vaccine Acceptancecontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding of low COVID-19 vaccine acceptance was inconsistent with what was reported from other university students in other countries like Saudi Arabia, [6]; Lebanon, [31]; Italy, [32]; Japan, [33]; the United Kingdome, [26]; Australia, [36] and France, [37] (90.4%, 87%, 86.1%, 85.5%, 73.5%, 60.5%, and 58.0%, respectively). Moreover, some studies were in line with our findings showed a low rate of COVID-19 vaccine acceptance like Turkey with 36.6% acceptance, [38]; Egyptian students 35%, [39]; Jordan with 34.9%, [22] and 33 % of the Iraqi university students [40].…”
Section: Factors Related To Covid-19 Vaccine Acceptancecontrasting
confidence: 99%
“…This variation in acceptancy rates could be explained as due to many factors including among others the differences in local culture, the severity of the pandemic in each country, the role of the government in encouraging the people to receive the vaccine, and the availability and accessibility of the vaccine in the country [33,39,41]. In Yemen, this is the first study conducted among university students, however, a study conducted in Mukalla city, Yemen among healthcare workers has reported a high percentage of COVID-19 vaccine hesitancy (74%), [21] which was much higher in comparison to our findings among students in the University of Aden (48.3%).…”
Section: Factors Related To Covid-19 Vaccine Acceptancementioning
confidence: 99%
“…Other authors report a significant increase in general confidence in vaccination among the Italian population one year into the pandemic [31]. Similarly, vaccine hesitancy is reported to have diminished in Turkey [32] and Japan [33]. However, in the USA, there has been a general reduction in favourable attitudes towards vaccination over the course of the pandemic [34], with attitudes worsening among Republican voters but remaining stable among Democrat voters.…”
Section: Discussionmentioning
confidence: 98%
“…Waszkiewicz et al [33] surveyed respondents about their vaccination intention at two time points and asked those who were previously vaccine hesitant to disclose the reasons behind their shifting mindset; main factors were increased concern about health and safety and a desire to travel. Evans et al [34] , Harada & Watanabe [35] , Hyland et al [36] , and Maciuszeket al [37] also surveyed respondents over time, identifying potential traits or beliefs at one wave that were associated with changes in vaccination intention at a later wave. Harada & Watanabe [35] found that those who shifted from hesitant to acceptant had higher COVID-19-related anxiety and lower concern for adverse vaccine side effects.…”
Section: Literature Reviewmentioning
confidence: 99%